Optimizing The Value Of BEI Infrastructure Companies: The Role Of Capital Structure, Asset Effectiveness, And Liquidity - Vini Fionita; Hartono Hartono (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This research investigates how capital structure (measured by DER), asset efficiency (measured by TATO), and liquidity (measured by CR) impact the corporate value of infrastructure firms listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. Adopting a quantitative methodology, secondary data were gathered from audited corporate annual reports. A purposive sampling technique selected 45 eligible companies out of 70, establishing 225 initial data points. Following the removal of extreme outliers using boxplot analysis, a final set of 156 observations was evaluated via multiple linear regression using SPSS 26. The simultaneous F-test reveals that all independent variables concurrently exert a significant effect on corporate value. Individually (t-test), both capital structure and liquidity show a significant negative relationship with firm value, whereas asset efficiency does not demonstrate any meaningful impact. These findings indicate that maintaining prudent financing strategies and optimizing working capital without over-leveraging are vital components for enhancing market valuation among investors in the infrastructure sector.